Nucleation and growth of ice crystals in the atmosphere - V. N. Golubev (Лëд и снег)
Nucleation of ice crystals in atmosphere is a result of condensation of water vapor on aerosol particle surface and heterogenic crystallization of the overcooled water micro-aggregations on surface irregularities. Crystal habit of ice nucleus and very small crystals (102 nm) corresponds to Gibbs–Wolf theorem and Thomson-Gibbs equation. Consequent growth of nucleated crystal is possible under condition of exceeding of water vapor concentration in atmosphere over the equilibrium vapor concentration over ice crystal. This equilibrium concentration for each crystal facet can be characterized by Clausius–Clapeyron relation with regard to its surface energy. The diagram of atmospheric ice crystals morphology in dependence from absolute and relative vapor supersaturation of atmosphere is developed. It is determined that the relation of height H and diameter D of atmospheric crystals increases at a growth of relative supersaturation, Δci/ci, but increases at a growth of absolute supersaturation, Δci = ci – ca. The alteration of H/D occurs gradually, which explains conditional character of delimitation on types on the base of this index. The field of absolute and relative supersaturation it is possible to subdivide relatively index H/D value in two parts: columnar forms area, where index H/D > 0.89 and lamellar forms area, where H/D < 0.89. Columnar and needle forms it is possible to characterize as low temperature forms, but lamellar, short-columnar and irregular forms – as high temperature forms. The variety of atmospheric crystal forms is subdivided on four basic groups: solid lamellar, solid columnar, dendrite lamellar and hollow columnar.